Assessing DNA Barcodes for Species Identification in North American Reptiles and Amphibians in Natural History Collections - Chambers, E. Anne (PLoS One, 2016)
BACKGROUND: High rates of species discovery and loss have led to the urgent need for more rapid assessment of species diversity in the herpetofauna. DNA barcoding allows for the preliminary identification of species based on sequence divergence. Prior DNA barcoding work on reptiles and amphibians has revealed higher biodiversity counts than previously estimated due to cases of cryptic and undiscovered species. Past studies have provided DNA barcodes for just 14% of the North American herpetofauna, revealing the need for expanded coverage. METHODOLOGY/PRINCIPAL FINDINGS: This study extends the DNA barcode reference library for North American herpetofauna, assesses the utility of this approach in aiding species delimitation, and examines the correspondence between current species boundaries and sequence clusters designated by the BIN system. Sequences were obtained from 730 specimens, representing 274 species (43%) from the North American herpetofauna. Mean intraspecific divergences were 1% and 3%, while average congeneric sequence divergences were 16% and 14% in amphibians and reptiles, respectively. BIN assignments corresponded with current species boundaries in 79% of amphibians, 100% of turtles, and 60% of squamates. Deep divergences (>2%) were noted in 35% of squamate and 16% of amphibian species, and low divergences (<2%) occurred in 12% of reptiles and 23% of amphibians, patterns reflected in BIN assignments. Sequence recovery declined with specimen age, and variation in recovery success was noted among collections. Within collections, barcodes effectively flagged seven mislabeled tissues, and barcode fragments were recovered from five formalin-fixed specimens. CONCLUSIONS/SIGNIFICANCE: This study demonstrates that DNA barcodes can effectively flag errors in museum collections, while BIN splits and merges reveal taxa belonging to deeply diverged or hybridizing lineages. This study is the first effort to compile a reference library of DNA barcodes for herpetofauna on a continental scale.